THE INFLUENCE OF TIKTOK LIVE STREAMING AFFORDANCE ON CONSUMER'S GIFT-GIVING AND PURCHASE INTENTION ON SOMETHINC BEAUTY PRODUCTS - Jihan Nurfaizah Alana; Osa Omar Sharif (SEAN Institute, 2023)
The popularity of live streaming on social media platforms and e-commerce, particularly on TikTok, has led to increased interest in purchasing products in Indonesia. Somethinc Beauty Products, a new brand established in 2019, has achieved remarkable sales and emerged as the top-selling beauty product in e-commerce. This study examines the impact of the Live Streaming strategy on TikTok on gift-giving and customer buying interest in Somethinc's beauty products. The research focuses on daily active TikTok users aged 16-55 who love shop online and have experience buying or watching Somethinc's live streaming within the past three months. A sample of 440 respondents was selected using purposive sampling. The data was collected through questionnaires and analyzed using SEM-PLS, considering variables such as Telepresence, Flow, Guidance Shopping, Metavoicing, Swift Guanxi, Purchase Intention, and Gift-Giving Intention. The findings indicate that Telepresence is negatively associated with Swift Guanxi, while Flow, Guidance Shopping, and Metavoicing are positively associated with Swift Guanxi. Swift Guanxi, in turn, positively influences both purchase intention and gift-giving intention. Future research should explore alternative indicators for the telepresence variable, consider different live streaming platforms and subjects, and incorporate additional variables for a more comprehensive understanding.